"Mamma mia": a compreensão do saber fazer cotidiano e a ressignificação dos papéis entre mulheres camponesas - Simonetti, Fernanda (2011)
This text is the result of an ethnographic study about peasant women in the city of Faxinal Soturno, which belongs to the region called Quarta Colônia ( Fourth Colony of Italian Immigration), in the central region of Rio Grande do Sul. Those peasant women are descendants of Italian immigrants who now live in two rural communities. Through ethnographic research, it was observed an understanding of know-how, formal education (and schooling), the changes in generations and in the patriarchal family, and how the influence of technology has been transforming these workers lives. Among these changes, it may be mentioned that the role of the woman inside these still markedly patrilineal families has undergone some changes over the years, such as: working besides home, having access to money (and consumerism) and a greater freedom in the communities, and leisure possibilities. As to the insertion of technology in their lives, it is viewed in a positive way since it helps them in everyday chores. In short, with this study, it can be stated that through observation and the peasants reports there was a considerable change in their lives in recent decades. This can either be observed in family relationships, as in the access to money and retirement, as well as in the growing appreciation and encouragement for their children s studies.